فعالية ترقية أخلاقيات الإشهارات التسويقية في حماية المستهلك من خلال أبعاد السياسة الجنائية للتشريع الجزائري - معراج, هواري; بوداود, بومدين (Revue jurisprudence; No 14 (2017): مجلة الاجتهاد القضائي, 2018)
سعى المشرع الجزائري في ظل مواكبة التحولات الكبرى والانفتاح الاعلامي الهائل لوسائط وتكنولوجيات الاعلام والاتصال الى مواكبة تسارع وتيرة سيرورتها وتأثيرها المباشر على اتجاهات وخيارات المستهلك الجزائري ب محاولة وضع حدود مفروضة على النشاط الترويجي الاشهاري ضمن مقاربة سياسة جنائية لا تهدف إلى حماية أصحاب الحقوق المنافسة فقط بل يتسع نطاقها لتنظيم الرسالة الإشهارية وفق ضوابط أخلاقيات هذا النشاط من جهة وعدم الحد من منطلقات الإبداع والابتكار فيه من جهة أخرى ـ بما يضمن ويحقق مبادئ العدالة الجنائية الاجتماعية المتوخاة، وذلك ما تضمنته مصادرها من خلال مجموعة من النصوص القانونية الوطنية، ومن خلال دفاتر الشروط الخاصة بكل سند إشهاري وهذا إلى جانب النصوص العامة المتعلقة بتعميم استعمال اللغة الوطنية وأحكام قانون العقوبات، ومراقبة مدى احترام هذه الحدود تمارس من قبل الهيئات المختصة كالمجلس الأعلى للإعلام ومجلس اخلاقيات المهنة مؤخرا إلى جانب القضاء الذي يسهر على تطبيق القوانين، بما يتضمن تنظيم محكم لشكل ومحتوى وطرق بث الرسائل الإشهارية . وذلك ما سنحاول دراسته   من خلال تبيان أبعاد ومقاصد السياسة الجنائية المرتبطة بأخلاقيات الاشهارات التسويقية ببعديها الوقائي والحمائي من جهة والجنائي الجزائي من جهة أخرى . الكلمات المفتاحية : الاشهار المضلل أو الخادع، السياسة الجنائية، العدالة الاجتماعية، الحماية الجزائية، حماية المستهلك . Abstract: Algerian legislature sought under cope with major shifts and opening the media's massive information and communications technologies to keep up with its acceleration and its direct impact on the attitudes of the Algerian consumer options and trying to put imposed limits on promotional activity for publicity within the approach to criminal policy does not aim to protect the rights holders of competition but also expanding to organize the message advertising spots according to the guidelines the ethics of this activity on the one hand and not to limit the perspectives of creativity and innovation in which the other hand, in order to ensure and achieve the principles of social criminal justice contemplated, and that the contents of the sources through a combination of national legal texts, and through the books of each support advertising conditions this along with the general provisions relating to circulate the use of the national language and the provisions of the Penal Code, and monitor respect for these limits practiced by the competent bodies like the old top for Media and ethics Council recently along with the judiciary, which ensures the implementation of laws, including the organization of an arbitrator to the form and content and methods of advertising spots broadcast messages. That is what we will try to study it by showing the dimensions and purposes of the criminal policy related to the ethics of advertising preventive and protective dimensions on the one hand and the Criminal Penal other.